2021
DOI: 10.1038/s41598-021-96201-1
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic experience during development establishes inter-individual differences in approach-avoidance behaviour of crickets

Abstract: Members of numerous animal species show consistent inter-individual differences in behaviours, but the forces generating animal “personality” or individuality remain unclear. We show that experiences gathered solely from social conflict can establish consistent differences in the decision of male crickets to approach or avoid a stimulus directed at one antenna. Adults isolated for 48 h from a colony already exhibit behavioural differences. Prior to staging a single dyadic contest, prospective winners approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…diminishing returns) fitness landscapes give rise to negative behaviour-state feedbacks promoting behavioural convergence among individuals, while convex fitness landscapes give rise to positive feedbacks resulting in behavioural diversification among individuals. While it is clear from empirical studies that developmental processes are crucial in influencing the spread of within- and among-individual variation [24,25], our model produces novel results that implicate the specific shape of the selective environment in the adaptive developmental programs generating patterns of individual variation. That said, nonlinear fitness functions have previously been shown to have major effects on the development and evolution of a range of traits, including foraging behaviours [26], risk assessment and management [27,28], life-history transitions [29], the use of heuristics in decision making [30], and social behaviours [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…diminishing returns) fitness landscapes give rise to negative behaviour-state feedbacks promoting behavioural convergence among individuals, while convex fitness landscapes give rise to positive feedbacks resulting in behavioural diversification among individuals. While it is clear from empirical studies that developmental processes are crucial in influencing the spread of within- and among-individual variation [24,25], our model produces novel results that implicate the specific shape of the selective environment in the adaptive developmental programs generating patterns of individual variation. That said, nonlinear fitness functions have previously been shown to have major effects on the development and evolution of a range of traits, including foraging behaviours [26], risk assessment and management [27,28], life-history transitions [29], the use of heuristics in decision making [30], and social behaviours [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…This seems likely, considering that a similar situation has been reported for classical conditioning of honey bees, where the population comprises two types of animals, those that have acquired a conditioned response, and those that have not (Pamir et al, 2011 ). Furthermore, we have already demonstrated that crickets taken from standard breeding colonies show consistent inter-individual differences with respect to their general motility, exploratory behaviour, aggressiveness and their decision to approach or avoid a novel stimulus, resulting in basically two ethotypes comprising aggressive-proactive and submissive-reactive individuals (Rose et al, 2017 ; Balsam and Stevenson, 2020 , 2021 ). Notably, these differences appear to arise as a result of social experience, in particular social subjugation by aggressive adult males during development (Balsam and Stevenson, 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have already demonstrated that crickets taken from standard breeding colonies show consistent inter-individual differences with respect to their general motility, exploratory behaviour, aggressiveness and their decision to approach or avoid a novel stimulus, resulting in basically two ethotypes comprising aggressive-proactive and submissive-reactive individuals (Rose et al, 2017 ; Balsam and Stevenson, 2020 , 2021 ). Notably, these differences appear to arise as a result of social experience, in particular social subjugation by aggressive adult males during development (Balsam and Stevenson, 2020 , 2021 ). Accordingly, we are currently testing the hypothesis, that aggressive social experience has a major impact on individual learning capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the cavy (Cavia aperea), variation in birth season (associated with different stressors) leads to behavioral syndrome differences in adults (Guenther et al, 2014). In crickets, agonistic experience during development shapes individual differences in approach-avoidance behaviors, aggressiveness, and motility, which the authors argue supports a proactive and reactive coping style syndromes in that species (Balsam and Stevenson, 2021). The social environment can represent different levels of stress, and certainly variation in the type of mating interactions is likely to be a large source of stress variation.…”
Section: Sexual-social Rearing Environment Shaping Behavioral Syndromesmentioning
confidence: 92%